2020
DOI: 10.1186/s40364-020-00205-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma circulating tumor DNA assessment reveals KMT2D as a potential poor prognostic factor in extranodal NK/T-cell lymphoma

Abstract: Background: The early detection of tumors upon initial diagnosis or during routine surveillance is important for improving survival outcomes. Here, we investigated the feasibility and clinical significance of circulating tumor DNA (ctDNA) detection for Extranodal NK/T-cell lymphoma, nasal type (ENTKL). Methods: The plasma ctDNA assessment was based on blood specimens collected from 65 newly diagnosed patients with ENKTL in the hematology medical center of Xinqiao Hospital. Longitudinal samples collected under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Similar to our results, studies by Herrera et al also showed a correlation between ctDNA and disease progression as well as recurrence, whose multivariable model results show that detectable ctDNA was associated with increased risk of progression/death (HR 3.9, P = 0.003) and relapse/progression (HR 10.8, P = 0.0006) ( 29 ). Moreover, some studies indicated that detectable ctDNA was also associated with tumor volume, which means ctDNA is associated with tumor burden in patients ( 11 , 24 ). Given the non-invasive nature and short half-life of ctDNA, its interim monitoring during therapy can provide a real-time assessment of tumor dynamics, allowing for an early indication of response or resistance to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, studies by Herrera et al also showed a correlation between ctDNA and disease progression as well as recurrence, whose multivariable model results show that detectable ctDNA was associated with increased risk of progression/death (HR 3.9, P = 0.003) and relapse/progression (HR 10.8, P = 0.0006) ( 29 ). Moreover, some studies indicated that detectable ctDNA was also associated with tumor volume, which means ctDNA is associated with tumor burden in patients ( 11 , 24 ). Given the non-invasive nature and short half-life of ctDNA, its interim monitoring during therapy can provide a real-time assessment of tumor dynamics, allowing for an early indication of response or resistance to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of NHL, the genetic analysis of plasma cfDNA found that when detecting mutations that were detected at frequencies of greater than 20% in biopsy tissue, the sensitivity was 88.0%, and the specificity was greater than 99% ( 62 ). The consistencies of gene mutations detected among ctDNA and biopsied tissues from extranodal NK/T-cell lymphoma (nasal type), T-cell lymphoblastic lymphoma, and angioimmunoblastic T-cell lymphoma were 93.75%, 89.1%, and 83%, respectively ( 63 65 ). The above results indicated that cfDNA/ctDNA could be used to assess the tumor genotypes of NHL patients as alternative methods for tissue biopsy.…”
Section: Lbs In Tumor Genotyping and Cell-of-origin Classificationmentioning
confidence: 99%
“…The study also confirmed that cfDNA concentration and integrity are significantly related to the Eastern Cooperative Oncology Group (ECOG) score, LDH level, disease stage, IPI score, and B symptoms ( 69 ). In addition, higher concentrations of ctDNA have been significantly correlated with total metabolic tumor volumes, assessed by positron emission tomography/computerized tomography (PET/CT), in both DLBCL and extranodal NK/T-cell lymphoma ( 59 , 63 , 66 , 70 ), indicating that ctDNA levels might serve as a surrogate for tumor burden. Many studies have confirmed that high levels of cfDNA/ctDNA in NHL, including DLBCL, FL, TCL, and NKTCL, are associated with shorter progression-free survival (PFS) and overall survival (OS) ( 33 , 34 , 36 , 59 , 71 , 72 ), which indicates that high cfDNA/ctDNA concentrations are poor prognostic factors for NHL.…”
Section: Lbs As Biomarkers For Prognosismentioning
confidence: 99%
“…MCL patients with KMT2D mutations have higher β2microglobulin, higher frequency of B symptoms, and bulky disease [90]. KMT2D mutations are also detected in 18-23% of NKTCL patients and related to poor prognosis [91,92].…”
Section: Kmt2mentioning
confidence: 99%